Application of nine air-dried Capsicum annum cultivars as food preservative: Micronutrient content, antioxidant activity, and foodborne pathogens inhibitory effects. Issue 4 (3rd April 2017) - Loizzo, Monica Rosa; Bonesi, Marco; Serio, Annalisa; Chaves-López, Clemencia; Falco, Tiziana; Paparella, Antonello; Menichini, Francesco; Tundis, Rosa
ABSTRACT: Capsicum annum cultivars Yellow cayenne, Portafortuna, Idealino, Sole, Duemila, Pellegrino, Fantasia, Loco, and Effix were investigated for their antioxidant properties and foodborne pathogens inhibitory activity. The total phenols, flavonoids, anthocyanins, capsaicinoids, carotenoids, ascorbic acid, and vitamin E content were also determined. Duemila and Portafortuna cultivars showed the highest total phenol content with values of 924.3 and 935.0 mg of chlorogenic acid equivalents/100 g dried weight, respectively. Idealino pepper presented the highest capsaicin content (2932.1 μg/g dried weight). The antioxidant capacity was evaluated by using 2, 2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid test, 2, 2-diphenyl-1-picrylhydrazyl test, and ferric reducing ability power assay. Both Pellegrino and Idealino samples exhibited a promising radical scavenging ability against 2, 2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid radical with IC50 values of 45.2 and 45.7 μg/mL, respectively. All the extracts were able to inhibit the growth of Staphylococcus aureus and Listeria monocytogenes investigated strains. The most active are Effix and Fantasia peppers with minimal inhibitory concentration between 12.5 and 25.0 mg/mL, respectively. Overall, these results support the use of these pepper species as dried extract in food preservation.